Improvement of PT Bank XYZ Automatic Teller Machine (ATM) Quality of Service Through Information Technology Risk Management - Nugraha, Risky; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
Technology has become one of the important factors in supporting an organization operational, especially in banking industry that relied heavily on information technology. Automatic Teller Machine (ATM) is one of bank e-channel products that provide the customers with the services that equal as doing transaction at the branch offices for 24x7 hours – spread throughout strategic location in all over Indonesia. With more than 6,000 ATMs that are spread throughout Indonesia, the banks can served billion rupiah of daily transactions that contributed as one of the banks source of revenue and also as one of its competitive advantage. In an attempt to increase its ATM quality of services as one of its competitive advantage, Bank XYZ periodically conduct internal audit on the ATM system to ensure the internal control is appropriate in protecting customer’s data integrity and security while doing transaction. However, as time goes, the ATM system is also becoming more complex that cause the conventional audit method is not enough to detect flaws or weaknesses on the system that still exist and then improve it. It requires a new method to evaluate the system from banking services point-of-view. Risk-based audit method that is focused in ATM services, enable Bank XYZ to identify risks for each possible scenario when customer doing a transaction at ATM. By using that method, it is expected to improve Bank XYZ ATM quality of services to fulfill its ATM level of service claim – 24x7 hours of banking services through risk mapping prioritization method. Keywords: ATM, Information System, IT Audit, IT Risk Management